Regional nerve block decreases opioid use after complete sternal‐sparing left ventricular assist device implantation. Issue 5 (24th March 2019) - Ayers, Brian; Stahl, Rachel; Wood, Katherine; Bernstein, Wendy; Gosev, Igor; Philippo, Sean; Lebow, Brandon; Barrus, Bryan; Lindenmuth, Danielle
Abstract: Background: Less‐invasive techniques for left ventricular assist device (LVAD) implantation have shown promising outcomes but are associated with significant postoperative pain. We aim to investigate the use of ultrasound‐guided regional nerve blocks to improve pain management during these procedures. Methods: We retrospectively reviewed patients implanted with a HeartMate 3 LVAD via complete sternal‐sparing (CSS) approach at our institution from February 2018 to July 2018. Patients were grouped based on their postoperative pain management plan—those who received a regional nerve block plus multimodal analgesia and a control group who received standard multimodal analgesia alone. Pain scores and analgesic use were recorded for all patients during the initial 72 hours postoperatively. Results: Preoperative characteristics were similar between cohorts. Of the 28 patients included in the study, 15 (54%) received a postoperative regional nerve block. Patients who received a nerve block had significantly lower pain scores and required a lower dose of opioid analgesics (70.7 ± 13.9 vs 124.6 ± 19.3 morphine equivalents, P = 0.029) during the first 72 hours postoperatively. There was no difference in time to extubation, intensive care unit length of stay, or hospital length of stay. Conclusions: Optimizing postoperative analgesia using a regional nerve block is associated with decreased opioid use and decreased postoperative pain after CSS LVAD implantation. Regional nerve blocks should be included as part of a protocol‐based postoperative pain management program.